The relationship between dividend policy and earnings management: A~causality analysis - Olfa Ben Salah; Anis Jarboui (Journal of Economics, Finance and Administrative Science, 2024)
Purpose - The objective of this paper is to investigate the direction of the causal relationship between dividend policy (DP) and earnings management (EM). Design/methodology/approach This research utilizes the panel data analysis to investigate the causal relationship between EM and DP. It provides empirical insights based on a sample of 280 French nonfinancial companies listed on the CAC All-Tradable index during the period of 2008-2015. The study initiates with a Granger causality examination on the unbalanced panel data and employs a dynamic panel approach with the generalized method of moments (GMM). It further estimates the empirical models simultaneously using the three-stage least squares (3SLS) method and the iterative triple least squares (iterative 3SLS) method. Findings The estimation of our various empirical models confirms the presence of a bidirectional causal relationship between DP and EM. Practical implications Our study highlights the prevalence of EM in the French context, particularly within DP. It underscores the need for regulatory bodies, the Ministry of Finance, external auditors and stock exchange organizers to prioritize governance mechanisms for improving the quality of financial information disclosed by companies. Originality/value This research is, to the best of our knowledge, the first is to extensively investigate the reciprocal causal relationship between DP and EM in France. Previous studies have not placed a significant emphasis on exploring this bidirectional link between these two variables.
Keywords: 330; Bidirectional causality; DP; EM; Granger causality; Simultaneous equation models